(untitled) (Zaporizhzhia Historical Review, 2021)
The discuss problems concerning the determination the political forces, which initiated the organization of the Ukrainian Central Council in 1917 are actualized by the author in this article. The author comes to the conclusion, that the process of the Ukrainian statemaking in the beginning of 1917 was the result of the interaction of the representatives of the various political forces both the socialistic and independent orientation.